Hyper-stretchable self-powered sensors based on electrohydrodynamically printed, self-similar piezoelectric nano/microfibers. (October 2017) - Huang, YongAn; Ding, Yajiang; Bian, Jing; Su, Yewang; Zhou, Jun; Duan, Yongqing; Yin, Zhouping
Abstract: Hyper-stretchable self-powered sensors with high sensitivity and excellent stability using low-cost, printable, organic nanomaterials are attractive for immense applications. Here we present self-similar piezoelectric nano/microfibers for a hyper-stretchable self-powered sensor that demonstrates high stretchability (> 300%), low detection limit (0.2 mg), and excellent durability (> 1400 times at strain 150%). A proposed helix electrohydrodynamic printing technique (HE-Printing) in combination with in-surface self-organized buckling is used to fabricate aligned self-similar poly[vinylidene fluoride] (PVDF) nano/microfibers with in situ mechanical stretch and electrical poling to produce excellent piezoelectric properties. The hyper-stretchable self-powered sensors have shown repeatable and consistent electrical outputs with detection limit an order of magnitude smaller than the other stretchable sensors. Additionally, such sensors can simultaneously measure the own status and the extra multiply physical quantities, such as lateral pressure, impulse rate and applied strain. The high sensitivity can be further utilized to remotely detect human motion in addition to sensing a piece of paper with 1 mm × 1 mm. Further the fiber-based sensors can avoid the catastrophic collapse or wrinkling of serpentine film-based structure during stretching. Graphical abstract: Highlights: The self-powered sensor demonstrates ultra-high stretchability (> 300%) and ultra-low detection limit (0.2 mg). Helix electrohydrodynamic printing is proposed to fabricate the sensor in a low-cost, large-scale and aligned manner. The sensor can simultaneously measure multiply physical quantities of the own status and extra mechanical stimuli.